Elongation mechanism and substrate specificity of 2',5'-oligoadenylate synthetase. - Justesen, J (1980)
2',5'-Oligoadenylate synthetase has been purified from a rabbit reticulocyte lysate to a high degree of purity. The enzyme contained no detectable interfering activities that could degrade the nucleoside triphosphate substrate or the oligomeric products. Two basic properties of this enzyme have been examined: the elongation mechanism for the synthesis of oligoadenylates and the substrate specificity for nucleotides. Kinetic studies on the formation of different oligomeric intermediates show that the dimer pppA2'p5'A is the first product to accumulate in predominant proportion during the first period of reaction; the trimer and other longer oligomers appear after a lag phase. The amount of the trimer increases at the expense of the dimer. Preformed dimers and trimers added to the incubation mixture were readily incorporated into higher oligomers, suggesting the free access of these dimers and trimers to the active center after the onset of polymerization of ATP. The results indicate clearly that the enzyme catalyzes the de novo synthesis of the oligonucleotide from ATP and that the mechanism of elongation of the 2',5'-oligonucleotides catalyzed by the enzyme is not processive. Polymerization of a mixture of ATP and another nucleoside triphosphate shows that the enzyme is not only an ATP polymerase. The 2',5'-oligoadenylate synthetase is in fact a 2',5'-nucleotidyltransferase that catalyzes the formation of co-oligonucleotides. However, the purified reticulocyte enzyme catalyzed only the addition of one unit of GMP, UMP, CMP, 2'-dAMP, 3'-dAMP, dCMP, dGMP, or TMP to the 2'-OH end of a preformed oligoadenylate. A procedure for the separation of 2',5'-oligonucleotides with or without the 5'triphosphate end also is described.